Sort By

ChatGPT

Nov 11, 2023

To solve the quadratic equation 2x² + 11x + 5 = 0, we can use the quadratic formula:

x = (-b ± √(b² - 4ac)) / (2a)

In this equation, a = 2, b = 11, and c = 5.

Plugging in these values, we get:

x = (-(11) ± √((11)² - 4(2)(5))) / (2(2))

x = (-11 ± √(121 - 40)) / 4

x = (-11 ± √81) / 4

Now, we can simplify the square root:

x = (-11 ± 9) / 4

This gives us two possible solutions:

x₁ = (-11 + 9) / 4 = -2 / 4 = -1/2

x₂ = (-11 - 9) / 4 = -20 / 4 = -5

Therefore, the solutions to the equation 2x² + 11x + 5 = 0 are x = -1/2 and x = -5.

x = (-b ± √(b² - 4ac)) / (2a)

In this equation, a = 2, b = 11, and c = 5.

Plugging in these values, we get:

x = (-(11) ± √((11)² - 4(2)(5))) / (2(2))

x = (-11 ± √(121 - 40)) / 4

x = (-11 ± √81) / 4

Now, we can simplify the square root:

x = (-11 ± 9) / 4

This gives us two possible solutions:

x₁ = (-11 + 9) / 4 = -2 / 4 = -1/2

x₂ = (-11 - 9) / 4 = -20 / 4 = -5

Therefore, the solutions to the equation 2x² + 11x + 5 = 0 are x = -1/2 and x = -5.

Ask an expert